Enhanced electrocatalytic hydrogen evolution in graphene via defect engineering and heteroatoms co-doping. (20th November 2016) - Tian, Ye; Mei, Rui; Xue, Da-zhong; Zhang, Xiao; Peng, Wei
Abstract: Development of efficient and metal-free electrocatalysts toward hydrogen evolution reaction (HER) is of great significance for the renewable energy conversion and storage technologies. Heteroatom doping, especially two heteroatoms co-doping, is one of the most effective strategies to improve the catalytic activity of carbon-based electrocatalysts. Here, we reported that the plasma-etching could produce additional structural defects on N, S co-doped graphene (NSG), which further improved the HER activity of NSG. It was demonstrated that the synergetic coupling effect of N, S co-doping and plasma-induced structural defects could maximize the number of exposed active sites and significantly enhance the HER activity of graphene in both acidic and alkaline media. This study thus indicates that combining defect engineering with heteroatoms co-doping is an efficient strategy for dramatically improving the HER activity of graphene.